Product design in the sustainable era. - Wiedemann, Julius, ....- (Köln : Taschen, 2010)
Sustainability is not a passing fashion, and people are constantly searching for more information, products and innovations in this area. Designers, in turn, are responding with elegant, efficient, low-impact products that look towards a sustainable future. This book brings together over 100 such innovative and award-winning projects from over 20 countries, launched by leading design offices and companies worldwide, including IDEO, IBM, and New Deal Design.